Societal entrepreneurship and competitiveness - Dana, Leo-Paul; Ratten, Vanessa (Emerald Publishing Limited, 2019)
Societal Entrepreneurship and Competitiveness examines the role of society in the creation of entrepreneurial opportunities. As society undergoes demographic shifts, cultural change and technological advancement, the way individuals, companies and institutions see and react to entrepreneurship also diversifies. Chapters explore alternative dimensions of entrepreneurship by considering different societal components and assessing attitudes towards entrepreneurship, specifically in terms of competition. By focusing on competitiveness, the book provides new conceptual approaches to understanding societal entrepreneurship and considers future developments. Utilizing an international and interdisciplinary approach to examining contemporary societal entrepreneurship, the book includes research on areas such as student entrepreneurship within Australian Universities, technology-based entrepreneurship within Turkey, and microfinance and necessity entrepreneurship within Ghana. The book will benefit researchers working in the fields of sociology, anthropology and business management, and will develop practitioners' understanding of the impact society has on entrepreneurship and entrepreneurial behavior.